The Potential of Bisphosphonate Risedronate Hydrogel in Preventing Relapse Movement - Utari, Tita Ratya; Pudyani, Pinandi Sri; Ana, Ika Dewi; Asmara, Widya (2022)
Objectives: To analyze the effect of risedronate hydrogel on enzyme alkaline phosphatase (ALP) and osteoclast/osteoblast ratio during tooth relapse movement Materials and methods: The research design is experimental with time series. The lower incisors of 75 guinea pigs are distally moved using open coil spring. The guinea pigs were divided into three groups: without risedronate (group A; n = 25); given 250 μmol/L of risedronate hydrogel (group B; n = 25), and given 500 μmol/L of risedronate hydrogel (group C; n = 25). Risedronate were applied intrasulcularly in the mesial part of the gingival sulcus every 3 days. After 14 days of stabilization, the open coil spring was removed (bisphosphonate administration was continued). The relapsed teeth and ALP levels on days 0, 3, 7, 14, and 21 were measured. The osteoclast/osteoblast ratio was measured by hematoxylin and eosin staining. ANOVA test was used to determine the difference in the three groups and their interactions with concentration and time. Results: There was a significant difference in osteoclast/osteoblast ratio on day 3 and 14 the ratio was higher in group A than in groups B and C on day 3, and the ratio was higher in group C than in groups A and B on day 14. ALP levels were significantly different on day 14 and 21. Conclusions: The intrasulcular application of bisphosphonate risedronate affected the osteoclast/osteoblast ratio and increased ALP levels.